Ekonomi Politik Media Dalam YouTube Sebagai Ruang Publik Komunikasi Pariwisata Jawa Barat - Gayatri Atmadi; Udi Rusadhi Rusadhi (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The emergence of social media youtube with its practical, informative and efficient nature makes many people love it today. YouTube social media has many benefits, such as to search for movies, listen to music, watch the latest videos, and others. This study aims to explore the use of youtube according to the perspective of media political economy and Jurgen Habermas's thoughts on public sphere. Through a tourism communication approach, this research is included in the type of qualitative research with a discourse analysis research method based on storytelling video impressions produced by Kompas Daily entitled